A signature of renal stress resistance induced by short-term dietary restriction, fasting, and protein restriction (2017)
During kidney transplantation, ischemia-reperfusion injury (IRI) induces oxidative stress. Short-Term preoperative 30% dietary restriction (DR) and 3-day fasting protect against renal IRI. We investigated the contribution of macronutrients to this protection on both phenotypical and transcriptional levels. Male C57BL/6 mice were fed control food ad libitum, underwent two weeks of 30%DR, 3-day fasting, or received a protein-, carbohydrate-or fat-free diet for various periods of time. After completion of each diet, renal gene expression was investigated using microarrays. After induction of renal IRI by clamping the renal pedicles, animals were monitored seven days postoperatively for signs of IRI. In addition to 3-day fasting and two weeks 30%DR, three days of a protein-free diet protected against renal IRI as well, whereas the other diets did not. Gene expression patterns significantly overlapped between all diets except the fat-free diet. Detailed meta-Analysis showed involvement of nuclear receptor signaling via transcription factors, including FOXO3, HNF4A and HMGA1. In conclusion, three days of a protein-free diet is sufficient to induce protection against renal IRI similar to 3-day fasting and two weeks of 30%DR. The elucidated network of common protective pathways and transcription factors further improves our mechanistic insight into the increased stress resistance induced by short-Term DR. © The Author(s) 2017.